2019
DOI: 10.1002/ijc.32707
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake and risk of gastric cancer in the Stomach cancer Pooling (StoP) project

Abstract: The consumption of processed meat has been associated with noncardia gastric cancer, but evidence regarding a possible role of red meat is more limited. Our study aims to quantify the association between meat consumption, namely white, red and processed meat, and the risk of gastric cancer, through individual participant data meta-analysis of studies participating in the "Stomach cancer Pooling (StoP) Project". Data from 22 studies, including 11,443 cases and 28,029 controls, were used. Studyspecific odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 49 publications
1
40
1
2
Order By: Relevance
“…The exact mechanisms of fat‐free mass on cancer risk remain unclear and may vary among different cancer sites. A potential explanation is that fat‐free mass is associated with nutritional factors, such as red meat consumption, which is linked to risk of gastric cancer 19 . In addition, fat‐free mass may be associated with sex hormone, 20 insulin resistance, 21,22 which were likely to be linked with gastric cancer 23‐25 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms of fat‐free mass on cancer risk remain unclear and may vary among different cancer sites. A potential explanation is that fat‐free mass is associated with nutritional factors, such as red meat consumption, which is linked to risk of gastric cancer 19 . In addition, fat‐free mass may be associated with sex hormone, 20 insulin resistance, 21,22 which were likely to be linked with gastric cancer 23‐25 .…”
Section: Discussionmentioning
confidence: 99%
“…As for many other cancers, low socioeconomic status has also been identified as a risk factor for GC; in the latest StoP analysis, the pooled OR for the highest compared to the lowest level of education was 0.60 (95% CI, 0.44-0.84) [15]. With reference to dietary factors, data from the StoP project confirmed that meat consumption is a risk factor [16], whereas fruit intake is protective [17]. The interaction of all these environmental factors and HDGC, remains unquantified nowadays.…”
Section: Environmental Factors and Gcmentioning
confidence: 97%
“…In view of the high morbidity and mortality of GC, the study on the etiology of GC has attracted many scholars. Studies have shown that obesity, gastroesophageal reflux, unreasonable diet, Helicobacter pylori infection, and atrophic gastritis are all high-risk factors for GC [2][3][4]. At present, surgical resection of the tumor is still the main method for the treatment of GC in clinical practice [5].…”
Section: Introductionmentioning
confidence: 99%